2022
DOI: 10.1038/s41467-022-29023-y
|View full text |Cite
|
Sign up to set email alerts
|

Observation of solid-state bidirectional thermal conductivity switching in antiferroelectric lead zirconate (PbZrO3)

Abstract: Materials with tunable thermal properties enable on-demand control of temperature and heat flow, which is an integral component in the development of solid-state refrigeration, energy scavenging, and thermal circuits. Although gap-based and liquid-based thermal switches that work on the basis of mechanical movements have been an effective approach to control the flow of heat in the devices, their complex mechanisms impose considerable costs in latency, expense, and power consumption. As a consequence, material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
3
30
1
1
Order By: Relevance
“…Figure a compares the switching ratio of thermal conductivity in this work and previous reports ,,,, for FE materials. Note that the ratios in PbTiO 3 (navy leftward triangles) and BiFeO 3 (pink downward triangles) were obtained by the substrate strain engineering, which makes it difficult to realize reversible switching.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Figure a compares the switching ratio of thermal conductivity in this work and previous reports ,,,, for FE materials. Note that the ratios in PbTiO 3 (navy leftward triangles) and BiFeO 3 (pink downward triangles) were obtained by the substrate strain engineering, which makes it difficult to realize reversible switching.…”
Section: Resultssupporting
confidence: 56%
“…(a) Comparison of thermal conductivity switching ratio with the l –λ criterion in this work and previous reports. ,,,, (b) Application of 50/50 PZT as a thermal switch for the temperature control of the Li-ion battery. In the OFF state, 50/50 PZT has a low thermal conductivity while in the ON state, 50/50 PZT has a high thermal conductivity.…”
Section: Resultsmentioning
confidence: 76%
“…When an electric field is applied, more charges are induced around the nitrogen atoms, leading to phonon renormalization and the modulation of phonon anharmonicity through interatomic electrostatic interaction. Regarding the possibility of experimental implementation, the time-domain thermoreflectance technique could be used to measure the thermal transport properties under applied electric fields. Therefore, the results gained from this work unveil a new route of manipulating phonon hydrodynamics in ferroelectric materials at room temperature and beyond without affecting atomic structures, which provide an important guidance for designing layered materials with dynamically controllable thermal transport properties.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroelectric (FE) materials are one promising material system for thermal switching, as they have short switching time, wide range of working temperature, and large number of switching cycles. However, existing experimental studies on PbZr 0.3 Ti 0.7 O 3 , PbTiO 3 , and PbZrO 3 films [1,2] showed that the switching ratios of these FE materials are always less than 2 at room temperature. Recently, theoretical calculations have indicated that by employing crystal symmetry engineering, the thermal switching ratio of FE materials can be enhanced to 8.6 [3].…”
mentioning
confidence: 99%
“…Thus, one efficient strategy to improve the thermal switching performance is to modulate more than one parameter or to combine more than one modulation. The recent reports on combining structural phase transitions (C and v) and domain wall density changes (τ) [8], as well as antiferroelectric-ferroelectric and antiferroelectric-paraelectric phase transitions [2], indicate the potential of this strategy. For the other three factors, the properties of the material itself usually play a dominant role.…”
mentioning
confidence: 99%